The food of the Philippines : - Alejandro, Reynaldo (Periplus, 2005)
Filipino food, influenced by over 300 years of Chinese, Hispanic and American culinary techniques, is one of the most vibrant and intriguing cuisines in Asia. A tantalizing concoction of textures, flavors and colors, these popular Filipino recipes range from national dishes such as adobo, to the spicy dishes of the Bicol region. Genuine native artwork and a detailed description of life in the Philippines distinguish this title from other ethnic cookbooks. With all of the dishes and ingredients vividly photographed, you'll know just what to expect when preparing these exotic delicacies.